2006
DOI: 10.1161/01.atv.0000224325.96659.53
|View full text |Cite
|
Sign up to set email alerts
|

Less Effect of Intranasal Than Oral Hormone Therapy on Factors Associated With Venous Thrombosis Risk in Healthy Postmenopausal Women

Abstract: Objective-To compare the effects of intranasal and oral administration of 17␤-estradiol (E 2 ) and norethisterone (acetate) [NET(A)] in healthy postmenopausal women on activated protein C (APC) resistance and other hemostatic parameters associated with venous thrombosis. Methods and Results-In this 2-center, randomized, double-blind, 1-year trial, 90 postmenopausal women (56.6Ϯ4.7 years of age) received daily either an intranasal spray with 175 g/275 g E 2 /NET (nϭ47) or 1 mg/0.5 mg oral E 2 /NETA (nϭ43). No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
2
13
0
1
Order By: Relevance
“…Using transdermal HT, one study found a significant increase compared with baseline and placebo for unopposed transdermal E 2 (42) and the other found a nonsignificant decrease for transdermal E 2 plus oral micronized P (91). For intranasal E 2 plus NETA one study found a significant increase from baseline (100). In all studies, the effect of non-oral HT was significantly less when compared with the large increase in the oral HT group.…”
Section: Fertility and Sterility âmentioning
confidence: 87%
See 3 more Smart Citations
“…Using transdermal HT, one study found a significant increase compared with baseline and placebo for unopposed transdermal E 2 (42) and the other found a nonsignificant decrease for transdermal E 2 plus oral micronized P (91). For intranasal E 2 plus NETA one study found a significant increase from baseline (100). In all studies, the effect of non-oral HT was significantly less when compared with the large increase in the oral HT group.…”
Section: Fertility and Sterility âmentioning
confidence: 87%
“…One did not find an effect during unopposed transdermal E 2 or during oral HT (42), whereas the other reported a significant decrease from baseline during intranasal as well as oral E 2 plus NETA (100). Both studies found no difference between oral and non-oral therapy.…”
Section: Fertility and Sterility âmentioning
confidence: 87%
See 2 more Smart Citations
“…3 Several case-control studies demonstrated an increased incidence of venous thrombosis among HT users. [4][5][6][7][8] A meta-analysis performed by Meade 9 showed a higher incidence of venous thrombosis with HT, usually at the beginning of treatment. HT-triggered blood clotting modifications that contribute to thrombosis are particularly important to identify in women with other thrombotic risk factors, such as hereditary or acquired thrombophilia.…”
Section: Introductionmentioning
confidence: 99%